Initial approaches to the phenomenon of diasporic cultural identity in Junot Díaz’s The Brief Wondrous Life of Oscar Wao - Caycho Huapaya, Diana (2022)
This article seeks to analyze the mechanisms underlying the phenomenon of diasporic cultural identity in The Brief Wondrous Life of Oscar Wao, by Junot Díaz, through Stuart Hall’s approach. The construction of cultural identity from Hall’s point of departure is articulated from two axes: that of similarity/continuity and that of difference/rupture. In this way, the modalities in which both axes are manifested in the story are presented, in particular, from the tensions between Oscar and the dominicanidad. It is also argued that the identity fractures that arise in the construction of Oscar’s character are also reflected in the dislocated narrative structure of the work. From this, an initial approach to how the cultural identity of the diaspora affects the story both symbolically and formally is attempted.